The Role of the State in Legal Vacuum in Money Politics in Village Head Elections - Fratiwi, Feby; Suartini, Suartini; Fuad, Fokky (Universitas Muhammadiyah Sumatera Utara, 2025)
This study analyzes the legal vacuum in the village head election system using the rule of law theory approach. The village head election is an important part of a democratic village government system, where this process must reflect justice and applicable law. However, various legal vacuums often arise, such as unclear regulations, unfairness in the rules, and inconsistent law enforcement. The main problems discussed in this study are the factors that cause legal vacuums in village head elections and their impact on the sustainability of the principles of the rule of law, especially the supremacy of law, legal certainty, equality before the law, and access to justice. The method used in this study is a qualitative approach with document data analysis and literature studies. The rule of law theory is the basic framework for understanding the implications of legal vacuums on the stability of village democracy. The results of the study indicate that legal vacuums in village head elections can lead to injustice, abuse of power, and social conflict that damage the quality of village democracy. To overcome this problem, it is recommended to improve clearer regulations, training for stakeholders, and consistent law enforcement. This study is expected to contribute to legal reform and the improvement of a fairer, more transparent, and law-based village head election system.